Boken bakom storfilmen : hur amerikanska förlag använder sig av filmadaptioner för att sälja böcker - Svahn,Emma (2015)
The aim of this study is to describe how in the USA, book publishers and authors make use of film adaptations in the promotion of the books behind them. The investigation is based on the 22 books whose film adaptations made it into the top 100 of the American Box Office list from 2014, and it examines the film references that occur on the web pages created in order to promote these books. The result is analysed with a method inspired by Genette and his paratext theories. The theoretical frame of the investigation is, besides Genette, founded on adaptation theory (Hutcheon, 2013) and cross-promotion as explained by literary theory (Mitchell, 2007). The investigation shows, among other things, that there is an equal amount of actors on the book market who use a high amount, a medium amount, and a low amount of cross-promotion. The investigation also shows that the most common film references are tie in-covers and short textual references of the film. To generalize, the amount of cross-promotion used was due to factors such as the size of the publishing house, year of publication, genre, and whether the franchise included more film adaptations.
Keywords: marketing; cross-promotion; paratext; books; films; adaptation; publisher; author; Amazon; internet; box office